Two new species of Anax Leach, 1815 from the Solomon Islands and Tonga (Odonata: Aeshnidae) - Theischinger, Günther; Kalnins, Martins; Marinov, Milen (Zootaxa, 2024)
Species of the cosmopolitan genus Anax Leach, 1815 are among the largest dragonflies and the most powerful flyers. Within the genus the proportion between body length and wing and the body shape of both sexes are of great taxonomic importance. Here we describe two new Anax species: Anax insulanus sp. nov., from the Solomon Islands and A. tonga sp. nov., from Tonga. To distinguish both species from a very similar sympatric congener we compare the S3 Index which is defined as the relative length and width at its narrowest point of abdominal segment 3. Anax fumosus celebense Lieftinck, 1942 is raised to species level. Diagnostic characters of male and female (if available) are illustrated. A key is presented for the identification of the males of the 14 species of Anax known to occur in the Australian, the Oceanian and the south of the Indomalayan Biogeographical Realms.